2019
DOI: 10.1128/mra.01440-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of an Atypical Porcine Pestivirus Strain, GX01-2018, from Guangxi Province, China

Abstract: We report the complete genome sequence of an atypical porcine pestivirus (APPV) strain named GX01-2018 that was isolated in Guangxi Province, China, from a suckling piglet showing congenital tremor. The whole genome consisted of 11,565 bp and shared 83.4% to 98.2% nucleotide identities and 91.9% to 99.1% amino acid identities with other APPV strains from different countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…In the Americas, reports of APPV infection exist from Brazil [ 25 , 26 ], Canada [ 27 ] and the USA [ 7 , 8 , 28 ]. Asian APPV strains are available from China [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], Taiwan [ 14 ] and South Korea [ 39 ]. The highest sequence diversity to date has been detected in China.…”
Section: Phylogeny and Geographic Distribution Of Atypical Porcine Pestivirusesmentioning
confidence: 99%
“…In the Americas, reports of APPV infection exist from Brazil [ 25 , 26 ], Canada [ 27 ] and the USA [ 7 , 8 , 28 ]. Asian APPV strains are available from China [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], Taiwan [ 14 ] and South Korea [ 39 ]. The highest sequence diversity to date has been detected in China.…”
Section: Phylogeny and Geographic Distribution Of Atypical Porcine Pestivirusesmentioning
confidence: 99%
“…In the United States, APPV was first identified by NGS in pig serum samples collected in 2014 from five different states [ 1 ]. In subsequent years, several studies from different countries reported the circulation of APPV in the US [ 1 , 2 , 51 , 54 , 56 ], Germany [ 53 , 55 , 57 , 58 , 59 , 60 , 61 ], Netherlands [ 10 ], Sweden [ 62 ], Austria [ 50 ], England [ 63 ], China [ 38 , 42 , 44 , 46 , 47 , 61 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], Spain [ 41 , 74 ], South Korea [ 75 ], Brazil [ 16 , 48 , 49 , 76 ], Great Britain [ 61 ], Italy [ 43 , 61 ], Serbia [ 61 ], Switzerland [ 61 , 77 ], Taiwan [ 61 ], Canada [ 52 ], and Hungary [ 78 ].…”
Section: Atypical Porcine Pestivirusmentioning
confidence: 99%
“…(37) сообщили, что АПС в основном накапливается в подчелюстных лимфатических узлах новорожденных животных. В настоящее время инфекция АПС считается широко распространенной в Китае и обнаруживается почти во всех провинциях (63)(64)(65)(66).…”
unclassified